The Corrosion Properties of Zirconium and Titatium Loadbearing Implant Materials with Protective Oxide Coatings - Zykova, Anna; Safonov, Vladimir; Smolik, Jerzy; Rogowska, Renata; Lukyanchenko, Vladimir; Vyrva, Oleg; Yakovin, Stas (International Conference on Plasma Surface Engineering, 2013)
At present study the comparative analysis of parameters for oxide Al2O3 and ZrO2 films deposited by reactive magnetron sputtering (RMS) method on the load-bearing implant materials such as titanium-based (Ti4Al6V) and Zr has been made. The corrosion examinations of anodic polarization by potentiodynamic method, Tafel and Stern curves and also impedance method at SBF solution were presented.